The Galaxy Velocity Function from MIGHTEE-HI Early Science Data - Mulaudzi, Wanga (Department of Astronomy, 2022)
The velocity function of MIGHTEE-H I Early Science data is presented. This is the first velocity function that is based on a blind radio interferometric survey. As a precursor, understanding the systematics that affect the Early Science velocity function will optimise the full survey's analysis. PYMULTINEST and the Busy Function are employed to estimate the linewidths of the low spectral resolution data. The performance of PYMULTINEST in estimating known linewidths of simulated H I profiles with varying spectral resolution is assessed. The simulation study shows that the estimated linewidths of the Early Science data, using this novel method, are robust and are recovered within the uncertainty. The effects of cosmic variance, instrumental linewidth broadening and Doppler linewidth broadening on the velocity function are quantified within the context of the limitations of the Early Science data. The MIGHTEE-H I Early Science velocity function is compared with the velocity functions from previous large-scale H I surveys, namely the Arecibo Legacy Fast ALFA (ALFALFA) survey and the H I Parkes All-Sky Survey (HIPASS). There is general agreement with the ALFALFA and HIPASS results, when taking linewidth broadening into account, given that the MIGHTEE-H I Early Science data is strongly affected by cosmic variance. In particular, cosmic variance introduces an average uncertainty of ∼ 24% in the measured Early Science volume densities. The larger effective area of the full survey will reduce the impact of cosmic variance. The full survey velocity function can be further optimised by estimating the rotational velocities using kinematic modelling, and correcting the measured linewidths for instrumental broadening, Doppler broadening, turbulent motion and inclination effects.